Growth Hormone Stimulation Testing: To Test or Not to Test? That Is One of the Questions - Yau, Mabel; Rapaport, Robert (Frontiers in Endocrinology, 2022)
The evaluation of children with short stature includes observation over a prolonged period to establish a growth pattern as well as the exclusion of non-growth hormone related factors that affect growth. After a period of monitoring, evaluation, and screening, growth hormone stimulation testing is considered when the diagnosis of growth hormone deficiency (GHD) is entertained. Though flawed, growth hormone stimulation tests remain part of the comprehensive evaluation of growth and are essential for the diagnosis of growth hormone (GH) deficiency. Variables including testing length, growth hormone assay and diagnostic cut off affect results. Beyond the intrinsic issues of testing, results of GH stimulation testing can be influenced by patient characteristics. GH secretion is regulated by various factors including age, gender, puberty, nutritional status and body weight.